2019
DOI: 10.1093/carcin/bgz042
|View full text |Cite
|
Sign up to set email alerts
|

XB130 deficiency enhances carcinogen-induced skin tumorigenesis

Abstract: XB130 is an adaptor protein that functions as a mediator of multiple tyrosine kinases important for regulating cell proliferation, survival, migration and invasion. Formerly predicted as an oncogene, alterations of its expression are documented in various human cancers. However, the exact role of XB130 in tumorigenesis is unknown. To address its function in skin tumorigenesis, a two-stage dimethylbenzanthracene (DMBA)/12-O-tetradecanoylphorbol 13-acetate (TPA) study was performed on XB130 knockout (KO), hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Bai et al 3 explained that highly expressed XB130 is necessary for maintaining the normal physiological function of stomach and thyroid cells, and cancer cells with lowly expressed XB130 may manipulate the XB130‐mediated signal pathways that regulate cell proliferation, migration, and invasion to help tumor growth and invasion in gastric and thyroid cancers. Interestingly, XB130 has been shown to behave as a tumor suppressor in skin tumorigenesis induced by carcinogens recently and XB130 knockdown significantly promoted epidermal tumor cell proliferation 12 . Therefore, XB130 has attracted increasing interest from researchers due to its controversial effects on cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bai et al 3 explained that highly expressed XB130 is necessary for maintaining the normal physiological function of stomach and thyroid cells, and cancer cells with lowly expressed XB130 may manipulate the XB130‐mediated signal pathways that regulate cell proliferation, migration, and invasion to help tumor growth and invasion in gastric and thyroid cancers. Interestingly, XB130 has been shown to behave as a tumor suppressor in skin tumorigenesis induced by carcinogens recently and XB130 knockdown significantly promoted epidermal tumor cell proliferation 12 . Therefore, XB130 has attracted increasing interest from researchers due to its controversial effects on cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, XB130 has been predicted to be an oncogene and a potential diagnostic marker and therapeutic target for cancers 3,4 . But after that, in 2019, XB130 has been reported to be a tumor suppressor in skin tumorigenesis induced by carcinogen through inhibiting inflammation, 12 which was in contrast with previous conclusions and indicated that XB130 may play different roles in different tumors.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The study indicated tumor-suppressive functions of XB130. DMBA/TPA-treated XB130 KO male mice developed a higher number of skin tumors including dysplasia, verrucous dysplasia and keratoacanthoma [28]. Deficiency of XB130 dramatically increased epidermal tumor cell proliferation and enhanced the inflammatory response with accumulation of infiltrating neutrophils and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…XB130, a multifunctional adaptor protein, is an oncogene that mediates cell proliferation, migration and invasion in osteosarcoma, hepatocellular and esophageal squamous cell carcinoma and pancreatic ductal adenocarcinoma, as well as prostrate, breast and gastric cancer (15)(16)(17)(18)(19)(20)(21)(22). However, Cho et al (23) recently suggested that XB130 acts as a tumor suppressor in skin tumorigenesis by inhibiting inflammation, which indicates that XB130 may serve different roles in different types of tumor. Our previous study (24) demonstrated that, similar to miR-30 family members, XB130 silencing can inhibit cell migration, invasion and EMT in NSCLC.…”
Section: Introductionmentioning
confidence: 99%